Characterization of a novel lipase bound to the Geobacillus stearothermophilus AH22 membrane - Dincer, Barbaros; Iskender, Engin; Kizil, Demet; Adiguzel, Ahmet (Springer Heidelberg, 2025)
Lipases (EC 3.1.1.3), used in many industrial applications, hydrolyze tri-, di-, and monoglycerides to free fatty acids and glycerol. This study aimed to determine the capacity of Geobacillus stearothermophilus AH22 for membrane-bound lipase production and to identify the optimal medium for lipase production. Following the determination of certain parameters such as pH and temperature, where the produced membrane-bound lipase exhibits the best activity, the kinetic data, as Km and Vmax, were obtained in the presence of p-NPA (0.03 +/- 0.008 mM and 0.7 +/- 0.18 U), p-NPB (0.7 +/- 0.18 mM and 3.4 +/- 0.40 U), p-NPO (0.12 +/- 0.010 mM and 5.2 +/- 0.62 U), and p-NPL (0.01 +/- 0.003 mM and 0.8 +/- 0.15 U) substrates. The highest activity of AH22 membrane-bound lipase was observed at pH 9.0 in the presence of substrates, at temperatures ranging from 20 to 40 degrees C for substrates with low carbon chains fatty acids and from 50 to 60 degrees C for substrates with long carbon chains. Also, it was observed that the cells dried by lyophilization showed lipase activity after they were pulver-ized. However, in terms of reuse, it was determined that wet cells were more efficient than powdered cells. It was found that the activity of the AH22 membrane-bound lipase had not changed much in the presence of anions and cations but decreased significantly in the presence of detergents and beta-mercaptoethanol. The AH22 membrane-bound lipase can be directly used in other industrial areas where lipase is used, except for the detergent industry, without requiring additional and expensive processing such as purification or immobilization.
Keywords: Geobacillus stearothermophilus; Thermophilic bacteria; Membrane-bound lipase; Industrial enzymes